Klinik Pelatihan: Strategi Meningkatkan Skor TOEFL Siswa SMA Kelas 12 untuk Persiapan Studi Lanjut - Hilman Hilman; Tito Parta Wibowo; Ifan Juniyanto; Ayu Rahmawati; Siti Rani; Irawati Irawati; Fadilah Fadilah (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
This Community Service Program (Pengabdian Kepada Masyarakat/PKM) aims to provide training and practical experience for twelfth-grade senior high school students to enhance their understanding of answering TOEFL-related questions in preparation for further studies, both domestically and internationally, which require a minimum TOEFL score. The program is conducted at SMA Negeri 1 Ciruas and targeted Grade XII students. The implementation of this PKM employs several methods, including a preliminary survey, TOEFL training sessions, and a post-training comprehension survey. The training activities are carried out over four days, from March 4 to March 7, 2025. The results of the program indicates a significant improvement in students’ understanding of TOEFL question strategies, with an increase of 80%, representing 21 out of 26 participating students. Among the three TOEFL sections—Listening, Structure, and Reading—the most notable improvements are observed in the Structure and Reading sections.